Jaminan Aksesibilitas Penyandang Disabilitas Netra atas Layanan Kenotariatan Berdasarkan Teori Kepastian Hukum - RIALITA FEBRINA (Jurnal Hukum Lex Generalis, 2025)
This research is entitled "Guaranteeing Accessibility for Persons with Disabilities to Notarial Deeds Based on the Theory of Legal Certainty." The study aims to analyze the regulations governing the guarantee of notarial services for persons with disabilities and to evaluate whether these regulations comply with the principles of legal certainty theory. The theory applied in this research is the theory of legal certainty. The research method used is the normative juridical method. The results indicate that there are legal instruments serving as the basis for accessibility guarantees. Existing laws emphasize the notary's obligation to provide services without discrimination but do not yet specifically regulate technical points to deliver inclusive services tailored to the needs of persons with visual disabilities.